Gender and groupwork - Cohen, Marcia B., 1950-; Mullender, Audrey (Routledge, 2003)
Based on practice experience in both the UK and the USA, Gender and Groupwork brings together the best of groupwork knowledge, skills and values in a true transatlantic partnership.